Allometric and Phylogenetic Aspects of Stapes Morphology in Ruminantia (Mammalia, Artiodactyla) - Mennecart, Bastien; Guignard, Coraline; Dziomber, Laura; Schulz, Georg; Müller, Bert; Costeur, Loïc (Frontiers in Earth Science, 2020)
The stapes is the smallest bone of the mammalian skeleton. Being the innermost middle ear ossicle, it is in contact with the inner ear and is directly responsible for sound transmission into it. Today, Ruminantia are one of the most diversified groups of large mammals with more than 200 species. However, their stapes has been very little studied. Here we investigate the shape of 66 stapes from 44 species of extant and extinct Ruminantia, including intra-individual and intra-specific observations, based on 3D tomographic data. Shape differences and similarities are quantitatively discussed thanks to 3D geometric morphometrics. The overall size of the stapes scales with a negative allometry in comparison to body mass. Moreover, the overall shape of the stapes informs about phylogeny. A trend is observed from a concave posterior crus with an enlarged stapes capitulum in Antilocapridae to a relatively straight posterior crus with a little reduced stapes capitulum in Cervidae, Bovidae being intermediate. In addition, the stapes of Antilocapridae is relatively trapezoid in lateral view; that of Cervidae is more triangular in lateral view; and that of Bovidae is relatively rectangular in lateral view. The stapedial footplate shape also gives phylogenetic information. The Tragulidae stapedial footplate is antero-posteriorly asymmetrical. The stapedial footplate is ovoid in stem Pecora. It is asymmetrical in Bovidae, while it is more symmetrical in Cervidae. This is in agreement with previous studies on the ruminant bony labyrinth showing that the oval window, the counterpart of the stapedial footplate on the inner ear, bears a strong phylogenetic signal already distinguishable in early Miocene ruminants.